Chimeric Antigen Receptor T Cells With Modified Interleukin-13 Preferentially Recognize IL13Rα2 and Suppress Malignant Glioma: A Preclinical Study - Kim, Kiwan; Gwak, Ho-Shin; Han, Nayoung; Hong, Eun Kyung; Choi, Beom K.; Lee, Sangeun; Choi, Soyoung; Park, Ju-Hwang; Seok, Ji-Hye; Jeon, Yeongha; Cho, Hyuntae; Lee, Song-Jae; et al. (Frontiers in Immunology, 2021)
Background Interleukin-13 receptor α 2 (IL13Rα2) is a promising tumor-directed antigen of malignant glioma (MG). Here, we examine the efficacy and safety of T cells containing a YYB-103 chimeric antigen receptor (CAR) that can preferentially bind to IL13Rα2 on MG cells. Methods IL13 was modified on the extracellular domain by substitution of amino acids with E13K, R66D, S69D, and R109K and stably transfected into human T cells using a retroviral vector. The in vitro efficacy of YYB-103 CAR T cells was tested in cell lines with differing IL13Rα1 and IL13Rα2 expression. The in vivo efficacy of intracerebroventricular (i.c.v.) and intravenous (i.v.) routes of YYB-103 CAR T-cell administration were tested in orthotopic MG mouse models. Immunohistochemical staining of MG was performed using WHO grade 3/4 surgical specimens from 53 patients. IL13Rα2 expression was quantified by H-score calculated from staining intensity and percentage of positive cells. Results Binding affinity assay of YYB-103 verified apparently nil binding to IL13Rα1, which was more selective than previously reported IL13 modification (E13Y). YYB-103 CAR T cells showed selective toxicity toward co-cultured U87MG (IL13Rα1+/IL13Rα2+) cells but not A431 (IL13Rα1+/IL13Rα2−) cells. Consistently, YYB-103 CAR T cells suppressed tumor growth in nude mice receiving orthotopic injection of U87 MG cells. Both i.c.v. and i.v. injections of YYB-103 CAR T cells reduced tumor volume and prolonged overall survival of tumor-bearing mice. The median H-score for IL13Rα2 in patient-derived MG tissue was 5 (mean, 57.5; SD, 87.2; range, 0 to 300). Conclusion This preclinical study demonstrates the efficacy of IL13Rα2-targeted YYB-103 CAR T cells against MG cells. The use of modified IL13 to construct a CAR facilitated the selective targeting of IL13Rα2-expressing MG cells while sparing IL13Rα1-expressing cells. Notably, YYB-103 CAR T cells exhibited effective blood–brain barrier crossing, suggesting compatibility with i.v. administration rather than intracranial injection. Additionally, the high H-score for IL13Rα2 in glioblastoma, especially in conjunction with the poor prognostic markers of wild-type isocitrate dehydrogenase-1 (IDH-1) and unmethylated O6-methyl guanine methyl-transferase (MGMT), could be used to determine the eligibility of patients with recurrent glioblastoma for a future clinical trial of YYB-103 CAR T cells.